Success rate of dacryocystorhinostomy with and without silicone intubation: a comparative study - Parven, Sumona; Shipu, Zinat Rehana; Alauddin-Al-Azad, M.; Habib, M. As-Aad; Alam, Shirin Ara; Mukta, Kamrun Nahar (International Journal of Research in Medical Sciences, 2025)
Background: Dacryocystorhinostomy (DCR) is the gold standard operation for nasolacrimal duct obstruction, (NLDO) creating a bypass between the lacrimal sac and nasal cavity to restore tear drainage and alleviate epiphora. The role of silicone intubation as a method of improving surgical outcomes is contentious, with conflicting evidence regarding whether it is effective and necessary. Methods: The prospective comparative study was conducted at a tertiary care hospital in Dhaka, Bangladesh, from July 2019 to June 2024. Two hundred patients of chronic dacryocystitis were randomly placed in two groups: DCR with silicone intubation (n=100) and DCR without silicone intubation (n=100). Success was defined as freedom from epiphora, patent lacrimal passage on syringing, and no need for revision surgery. Data were analyzed using SPSS version 25, and statistical significance was established at p<0.05. Results: The age was 30.41±7.41 years in the silicone group and 31.98±7.55 years in the non-silicone group, with female predominance (62% vs 58%). Success was higher in the silicone intubation group (96%) compared to the non-silicone group (88%). Failure was 4% in the silicone group and 12% in the non-silicone group. Binary logistic regression revealed that silicone intubation increased the chance of success by 5.26 times (95% CI: 1.24-22.34, p=0.024), and it was the most significant predictor of surgical success. Conclusions: DCR with silicone intubation was more successful than DCR without intubation. High odds ratio supports the clinical benefit of routine silicone intubation for external DCR operations.